LAYANAN BIMBINGAN KARIER BERBASIS ONLINE MELALUI TEKNIK DISKUSI KELOMPOK DALAM PENGAMBILAN KEPUTUSAN KARIER SISWA SMA - Lisnawati Dewi; Euis Eti Rohaeti; Rima Irmayanti (IKIP Siliwangi, 2021)
Career decision-making is the process of determining one of two or more choices related to intentional work/further education. This research aims to find out how the Implementation of Online-based Career Guidance Services through Group Discussion Techniques in career decision making, teacher and student response, student difficulties, as well as obstacles experienced by BK teachers regarding Online-based Career Guidance services through Group Discussion Techniques in career decision making. The method study qualitative descriptive. Data obtained from results research in form words and explanations about a phenomenon that occurs. The subjects in this study were 1 BK Teacher, and 6 students of class XII Of State High School 1 Cisarua. The data collection procedure uses questionnaires, observations and interviews. Based on the results of research shows the findings in the field including students are not fully able to make career decisions well proven by the results of career decision making. There is only 1 student who has a career decision in the high category with a percentage of 17%, while 4 people with a moderate category with a percentage of 67%, and 1 person with a low category with a percentage of 17%. However, after being given career guidance services students find it helpful in their further education decision making. Keywords: Career Guidance, Group Discussion, Career Decision Making